2020
DOI: 10.1039/d0cb00099j
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic peptide scaffold with ability to stabilize and deliver a helical cell-impermeable cargo across membranes of cultured cancer cells

Abstract: A new helix-loop-helix peptide scaffold with dual ability to transport cargo across cancer cell membranes and disrupt mitochondrial membrane function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 51 publications
1
16
0
Order By: Relevance
“…cPF4PD (GCQAPLYKKI­IKKLLESGGX­GGAPLYKKII­KKLCES; X is azidoalanine) is a helix–loop–helix cyclic peptide with antimalarial properties. It enters infected red blood cells and cancer cells and reaches their cytosol without disrupting the cell membrane , and was here included to investigate whether it can deliver cargo peptides inside cancer cells. The linear CPP p18 was also conjugated to KD3 to assess its effect on the activity and cellular delivery of KD3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…cPF4PD (GCQAPLYKKI­IKKLLESGGX­GGAPLYKKII­KKLCES; X is azidoalanine) is a helix–loop–helix cyclic peptide with antimalarial properties. It enters infected red blood cells and cancer cells and reaches their cytosol without disrupting the cell membrane , and was here included to investigate whether it can deliver cargo peptides inside cancer cells. The linear CPP p18 was also conjugated to KD3 to assess its effect on the activity and cellular delivery of KD3.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Liu and collaborators found that conjugation of a CPP with PMI, a peptide that inhibits p53:MDM2/X interactions, induced cell membrane disruption at low concentrations, and therefore they employed liposome formulation as an alternative strategy to deliver PMI inside cells to reduce toxicity . In recent studies, we demonstrated the delivery of active p53 mimetics into the cytosol of cancer cells, followed by cell death without targeting p53:MDM2/X interactions; instead, cyclized CPP–cargo constructs induced toxicity via organelle/cell membrane disruption. , …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To decrease the number of possible isomers and avoid changes in the overall charge of Lys-rich peptides after labeling, the dye can be conjugated using site-directed strategies. Some examples include conjugation of alkyne-derivatized dyes onto azide-containing peptides with copper-catalyzed azide-alkyne cycloaddition, and conjugation of dyes containing hydroxylamine with acetone-linked peptides using oxime ligation ( 77 ).…”
Section: Distinguishing Internalized and Membrane-bound Peptide Via Flow Cytometrymentioning
confidence: 99%
“… 13 Along those lines, very recently it was demonstrated that conjugation of cCPPs via triazole linkages to the peptide KD3, which was known to be a non-cell permeable stapled peptide inhibitor of p53/MDM2 and p53/MDMX interactions, 14 enables activation of apoptosis in cancer cells. 15 Alternative approaches for creating cell-permeable peptides to disrupt p53/MDMX interactions using cyclic peptide scaffolds, 16 polycationic tags or medchem optimization strategies have been extensively studied. 17,18 …”
Section: Introductionmentioning
confidence: 99%